THE ROLE AND EFFECTIVENESS OF THE NATIONAL LEGAL DOCUMENTATION AND INFORMATION NETWORK AS A FORM OF PUBLIC SERVICE TO OBTAIN LEGAL - Vera Rimbawani Sushanty (NOMOI Law Review, 2022)
The provision of a National Law Database containing various integrated legal information is very important to realize the development of national law through the Law Reform Agenda Volume II. Legal information that is integrated, easy to access quickly and easily is very important as a raw material for legal development. The development of national law cannot be separated from the National Legal Documentation and Information (JDIHN) because the main purpose of its formation is to support and accelerate the development of national law. The purpose and usefulness of this paper is to determine the role and effectiveness of JDHIN as a form of public service to obtain legal information. The method used is descriptive analytical research. The discussion contains about JDHIN as a form of public service and the effectiveness of JDHIN to obtain legal information. The conclusion that can be drawn from this paper is that JDHIN is still ineffective because there are several inhibiting factors. Suggestions that the author can give include the need for new regulations for the management of the Legal Documentation and Information Network, policies and support from agency leaders in developing the Documentation Network, guidance for district/city JDIH members, the need for additional technical guidance training for members so that they can manage and understand the importance of the Legal Documentation and Information Network, the need for additional managers who manage the Legal Documentation and Information Network in accordance with their fields and additional budgets.